Utilización del modelo K en la gestión de una cadena de suministros para favorecer el crecimiento en los puntos de venta de los negocios retail de calzado - Asorza Nicho, Rosemary (2020)
This article offers a study of a retail footwear chain in Lima that uses the K-map method in its operations management. Its objectives are to verify if there is a positive impact on growth at the company’s points of sale, and to establish a relationship between the posed variables, considering the benefits of using the K-map method. The purpose of this study is to determine if this model promotes an increase in retail sales and if it is possible to recommend its use based upon hypotheses testing. This paper analyzes key performance indicators (KPIs) collected from six megastores to conduct normality, homogeneity, Pearson correlation and logistic regression testing. Results predict the relationship between variables and their influence on store growth with an efficacy of 83.3%.